Cardiovascular Responses to Psychosocial Stress Reflect Motivation State in Adults Born at Extremely Low Birth Weight. (5th March 2015) - Mathewson, Karen J.; Pyhälä, Riikka; Hovi, Petteri; Räikkönen, Katri; Van Lieshout, Ryan J.; Boyle, Michael H.; Saigal, Saroj; Morrison, Katherine M.; Kajantie, Eero; Schmidt, Louis A.
Background . Adults born extremely preterm appear to have more difficulty managing the stresses of early adulthood than their term-born peers. Objective . To examine the effects of being born at extremely low birth weight (ELBW; birth weight < 1000 g) versus at full term on cardiovascular responses to stress. Method . Cardiovascular responses were elicited during administration of a widely used laboratory stressor, the Trier Social Stress Test (TSST). Results . Term-born adults exhibited a larger decrease in total peripheral resistance and larger increase in cardiac output for TSST performance, reflecting greater resilience, than did ELBW adults. Furthermore, in ELBW participants but not controls, cardiovascular responses were correlated with anxiety, suggesting that their responses reflected feelings of stress. Conclusions . Skills-training and practice with relevant stressors may be necessary to increase the personal resources of ELBW participants for managing stress as they transition to adulthood.